2017
DOI: 10.1002/smll.201701437
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed Wide‐Bandgap Organic Semiconductor Nanostructures Arrays for Nonvolatile Organic Field‐Effect Transistor Memory

Abstract: In this paper, the development of organic field-effect transistor (OFET) memory device based on isolated and ordered nanostructures (NSs) arrays of wide-bandgap (WBG) small-molecule organic semiconductor material [2-(9-(4-(octyloxy)phenyl)-9H-fluoren-2-yl)thiophene]3 (WG ) is reported. The WG NSs are prepared from phase separation by spin-coating blend solutions of WG /trimethylolpropane (TMP), and then introduced as charge storage elements for nonvolatile OFET memory devices. Compared to the OFET memory devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 53 publications
1
90
0
Order By: Relevance
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
“…For example, for exciton transport in organic thin films, it is preferable to have a structure that is oriented normal to the π–π stacking direction to ensure optimized charge injection and/or extraction . Similarly, organic FETs (OFETs) are required to have a standing‐up molecular orientation, as opposed to the lying‐down orientation in organic LEDs (OLEDs) or organic PVs (OPVs) . In addition to the above‐described advantage, sequential deposition of different organic molecules allows more complex structures such as multicomponent or multidimensional 2D–organic heterostructures.…”
Section: Fabrication and Physical Properties Of 2d–organic Hybrid Strmentioning
confidence: 99%
“…Since the late 1940s, organic semiconductors have been extensively studied as promising candidates for scalable electronic and optoelectronic applications . Their physical and chemical properties are easily tunable owing to the availability of well‐established processing techniques as well as a wide selection of materials .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations